OPTIMIZATION OF STUDENT (SANTRI) MANAGEMENT IN THE DIGITAL ERA AT MODERN ISLAMIC BOARDING SCHOOLS - Nuryati; Ninuk; Patnahwati; Meity Suryandari (CV. Gerasi Insan Nusantara, 2026)
This study examines the optimization of student (santri) management in the digital era within modern Islamic boarding schools (pesantren). The research is motivated by the rapid development of information technology, which requires pesantren to adapt their management systems while maintaining Islamic values. This study employs a qualitative approach using a library research method by analyzing relevant literature on student management, Islamic education, and digital transformation. The findings reveal that student management in pesantren encompasses planning, organizing, implementation, supervision, and evaluation processes that are integrated with character building and academic development. In the digital era, optimization can be achieved through the digitalization of administrative systems, the implementation of pesantren management information systems, the use of digital learning platforms, and technology-based character development. These innovations enhance efficiency, transparency, and effectiveness in managing students. However, challenges such as limited technological infrastructure, low digital literacy, and concerns about negative impacts of technology remain significant. Therefore, a balanced integration between traditional pesantren values and digital innovation is essential to create adaptive, effective, and sustainable student management systems in modern pesantren.